A world atlas of translation - Gambier, Yves 1949-; Stecconi, Ubaldo (Amsterdam John Benjamins Publishing Company, 2019)
Intro; A World Atlas of Translation; Editorial page; Title page; Copyright page; Table of contents; Preface; Six consultants; Identifying traditions; Looking for translation; A World Atlas of Translation; Going through the steps; References; Chapter 1. Translating in the Pacific: Rendering the Christian Bible in the islanders' tongues; 1. Scope and terminology; 2. Current linguistic landscape; 3. How to say "Translate" in Pacific languages; 4. Early linguistic interactions and translation activities; 5. New focus of translation activities -- the Christian Bible
6. Recapitulation of a century (1818-1918) of Bible translation activities7. Translating the Christian Bible in the Pacific from 1918 to date; 8. Linguistic challenges faced by Pacific translators; 9. Conclusion: Looking forward to the future; References; Chapter 2. Recent tradition in Australia; 1. Preamble; 2. Overview; 3. The development of the concept of Translation; 4. Formalising translation; 5. Accreditation and training; 6. Translation in practice; 7. What is the concept of Translation in Australia?; 8. A notion of Translation?; References
Chapter 3. Japanese conceptualizations of 'translation'1. Introduction; 2. The impact of script: Translation as transposition and gloss reading; 3. Languages as fluid entities; 4. Introduction of European concepts of Translation; 5. The premodern professional norm with Dutch; 6. Translation as scholarly mining and interpretation; 7. Vernacular renditions of Chinese works; 8. Intralingual translations; 9. Inter-register translations; 10. Imitation as creativity; 11. Micro-level amalgams; 12. Translation as a two-stage process; 13. Moving 'mainstream'
14. Collaborative and surrogate translating and translator (in)visibility15. The allure of opacity; 16. The scope of 'Translation' in Japan; 17. Conclusion; References; Chapter 4. Contemporary scene of translation in China; 1. Introduction; 2. Sending-out, soft power, and translation as cultural exportation; 3. Commercialization, market economics, and translation as language service; 4. Unity, minority languages, and translation as accommodationist strategy; 5. Conclusion: Three keywords; References
Chapter 5. From plagiarism to incense sticks: The making of self and the other in translation history in Thai1. Introduction: Thainess and otherness; 2. Plae, prae, plian and plaeng: Translation in an etymology of change and transformation; 3. The Asian connections; 4. The age of Westernization: Translation as modernization, and plagiarism; 5. Burning incense sticks: The translator's fidelity and invisibility; 6. Conclusion; References; Funding information; Chapter 6. More or less "translation": Landscapes of language and communication in India; 1. Introduction; 2. Main challenging issues
Includes bibliographical references and indexes
Keywords: Translating and interpreting -- History; Language and culture; Translating and interpreting--History